(3TQM GdCRgQjIs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3NGdO Hf YHO Gddg GdGRgQj,J (B905 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdCMhGd hHYO ajbhd NGdO Hf YHO Gddg GdCRgQi Cf CTQM ebOeJi GdCRgQjI ai Yde GdYQHjI GdJi CedjJgG dHYV GdWdHg TQMkG dWjakG GdcdGe YfO GddZhjjf YHGQI Yf Gdbhd s
(3BNQgG (B:s
(3eJYdb CjVkG HjhShS GdfGS eVGa Edjg ef GdLfI eJYdb CjVkG HjhShS hGdfGS eYWha Ydi GdLfI hai gPG GdbOQ caGjg ddeHJOF hGdMeO ddg hMOg GdPi gOGfG dgPG heG cGfG dfgJOi dhdG Cf gOGfG Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs